Identification of deep intronic variants in 15 haemophilia A patients by next generation sequencing of the whole factor VIII gene - Bach, Elisa J.; Wolf, Beat; Oldenburg, Johannes; Müller, Clemens R.; Rost, Simone (Thrombosis and Haemostasis, 2015)
Current screening methods for factor VIII gene (F8) mutations can reveal the causative alteration in the vast majority of haemophilia A patients. Yet, standard diagnostic methods fail in about 2 % of cases. This study aimed at analysing the entire intronic sequences of the F8 gene in 15 haemophilia A patients by next generation sequencing. All patients had a mild to moderate phenotype and no mutation in the coding sequence and splice sites of the F8 gene could be diagnosed so far. Next generation sequencing data revealed 23 deep intronic candidate variants in several F8 introns, including six recurrent variants and three variants that have been described before. One patient additionally showed a deletion of 9.2 kb in intron 1, mediated by Alu-type repeats. Several bioinformatic tools were used to score the variants in comparison to known pathogenic F8 mutations in order to predict their deleteriousness. Pedigree analyses showed a correct segregation pattern for three of the presumptive mutations. In each of the 15 patients analysed, at least one deep intronic variant in the F8 gene was identified and predicted to alter F8 mRNA splicing. Reduced F8 mRNA levels and/or stability would be well compatible with the patients’ mild to moderate haemophilia A phenotypes. The next generation sequencing approach used proved an efficient method to screen the complete F8 gene and could be applied as a one-stop sequencing method for molecular diagnostics of haemophilia A.Note: The work was carried out at the Department of Human Genetics, University of Würzburg, Biocenter, Am Hubland, 97074 Würzburg, Germany. New
Keywords: Alternative splice sites; deep intronic variant; factor VIII; haemophilia A; next generation sequencing